Experimental data on the solar heating of a closed pool with polycarbonate cover: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Rivasplata Cabanillas, César Efraín (2020)
The heating of swimming pools using flat plate collectors of polyurethane, is a known practice in our environment, and has technical and economic justification, in places where there is excellent solar radiation, the water of the network is cold (05-15 °C), as well as the ambient temperatures descend at night about 5 to 10 ° C, requiring intensive use of the pool throughout the 12 months of the year, whether for recreational, tourist or therapeutic purposes- The aim of the heating of the pool is to achieve comfort temperatures in the pool water, in a range of 28-32 ° C, as well as to avoid the complementary consumption of electrical energy, and / or LPG, mainly along the coldest seasonal period of the year in southern Peru (April - August), thus extending the use of the pool to almost 12 months. An investment of this nature has a return on capital of less than 1 year and results in an investment in technical, economic and comfort terms. The coupling of a closed system on the pool that generates an external atmosphere for internal stay in the pool, produces an extreme greenhouse effect with temperatures and humidity in the air that is enclosed in this space, which must be controlled by control systems that activate the movement of air and humidity of this, so that room comfort temperatures are achieved when the user is out of the pool water. The acquired experimental data represents valuable information in the thermal analysis of a heated pool with solar collectors. with volumetric enclosure, which will allow to understand the thermal behavior of the air-water interaction in this type of systems, and that is different from that of an Outdoor heated pool.